An investigation on the effects of mutations in the ATG12 autophagy pathway of Arabidopsis thaliana - Damodaran, Ashvini (My University, 2007)
Under nutrient-deficient conditions, plants are forced to recycle secondary cellular constituents to conserve energy for the more essential processes (Klionsky, et al. 2000). Plants accomplish this through a process called autophagy, which involves the capture of cytosolic constituents in vesicles called autophagosomes and transportation of these vesicles to lytic vacuoles for degradation. Macroautophagy, the main autophagy pathway, requires an ATGI2-ATG5 protein conjugate for autophagosome formation (Thompson & Vierstra, 2005). Extensive research has been done on the ATG 12 pathway in organisms such as yeast, but research is yet to be done on ATG12 disruption in plants. By studying protein expression and performing phenotypic analysis oft he model plant Arabidopsis thaliana with mutationsinATG12and other members ofthe ATG12 pathway, we can begin to understand the role of the pathway in autophagic recycling during plant growth and development. Since autophagy controls many important aspects of crop physiology (e.g. seed germination, pathogen defense, and growth under nutrient-limiting conditions), this work will likely provide new venues for improving crop production.
21 p.
Keywords: Genetics